1996
DOI: 10.1007/bf00184860
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two nonculture antigen tests and three serotests for detection of anti-chlamydial antibodies in the diagnosis of ocular chlamydial infections

Abstract: PCR proved to be a good alternative to cell culture; DFA is useful for quick diagnosis. Genus-specific serotests cannot compete with chlamydial antigen detection. They differ in sensitivity and specificity because of the antigen type they present. They are still of only supportive value in cases where chlamydial antigen detection is not possible. Recently introduced species-specific antibody tests should be of greater value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
2
9
0
4
Order By: Relevance
“…After the age of 50, a significant decrease in the number of positive cases was witnessed in our study and this in accord with similar studies [10][11][12][13]. Our study was mainly based on adult chronic follicular conjunctivitis and we only had one pediatric case aged less than one year because neonates usually receive treatment in child therapeutic centers and are less frequently referred to ophthalmologic hospitals.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…After the age of 50, a significant decrease in the number of positive cases was witnessed in our study and this in accord with similar studies [10][11][12][13]. Our study was mainly based on adult chronic follicular conjunctivitis and we only had one pediatric case aged less than one year because neonates usually receive treatment in child therapeutic centers and are less frequently referred to ophthalmologic hospitals.…”
Section: Discussionsupporting
confidence: 90%
“…In our study from the total 285 patients referred to the lab, 109 of them (38.24%) were positive in terms of chlamydial infection. Similar studies have reported positive results of 8.6% and 38% in sample sizes of 93 and 100 patients, respectively [12,13]. It should be noted that neither our study nor others' detected a significant sex-based difference in chlamydial conjunctivitis contraction [2,9,11].…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Ein Hybridisierungstest (Gen-Probe®, Pfizer) und ein direkter Immunfluoreszenztest (Microtrak©, Syva) erwiesen sich am sensitivsten und spezifischsten. Eigene Untersuchungen mittels direkter Immunfluoreszenz an Lidbindehautabstrichen (Microtrak®, Syva) zeigten ebenfalls ausreichende Sensitivität und Spezifität im Vergleich zu Zellkultur und PCR [17].…”
Section: Diagnostikunclassified
“…Der Nachteil dieser Methoden liegt in den hohen Kosten, dem aufwendigen Laborequipment und der Tatsache, dass sie nicht als "patientside" Tests eingesetzt werden können [11]. Von den "Non-Culture"-Techniken kann die direkte Immunfluoreszenzfärbung an Lidbindehaut-Abstrichen für eine geringe Probenanzahl empfohlen werden [17,28]. Für eine exakte Auswertung ist allerdings eine gewisse Erfahrung auf dem Gebiet der Fluoreszenzmikroskopie unerlässlich.…”
Section: Diagnostikunclassified